(untitled) (Jurnal Akuntansi dan Keuangan, 2004)
Every activity in a certain company always deals with investing and financing decision. Financial management makes the investing and financing decision more effective in supporting the company’s growth. In order to see the effectiveness of investing and financing decision, financial management uses the financial ratio to analyze the numbers listed in the financial statements financial management measures the company’s growth base on sales changing. More over the company’s sustainable growth rate can be measured by balancing the investing and financing decision. In a success investing and financing decision can be measured by Return on Invested Capital (roic), Weighted Average Cost of Capital (WACC) and Economic Value Added (EVA). The matrix financial strategy is groups the companies into four quadrans and giving the company some strategic ideas to balance the company’s growth followed by investing and financing decision. Further more, the company’s growth can produce return to cover the financing cost. To apply the matrix financial strategy base on SWA and Mark Plus, 15 (fifteen) public companies with over one billion assets and 15 (fifteen) public companies wth bellow are used. one billion assets Abstract in Bahasa Indonesia : Setiap aktivitas perusahaan selalu bertumbuh pangkal pada keputusan investasi dan keputusan pembiayaan. Manajemen keuangan mengupayakan agar keputusan investasi dan keputusan pembiayaan menjadi lebih efektif dalam mendukung pertumbuhan perusahaan. Dalam upaya melihat efektivitas keputusan investasi dan keputusan pembiayaan, manajemen keuangan menggunakan analisis rasio keuangan untuk menganalisis angka yang tercantum dalam laporan keuangan. Pertumbuhan perusahaan dalam manajemen keuangan diukur berdasar perubahan penjualan, bahkan secara keuangan dapat dihitung berapa pertumbuhan yang seharusnya (sustainable growth rate) dengan melihat keselarasan keputusan investasi dan pembiayaan. Dalam analisis rasio keuangan ukuran keberhasilan keputusan investasi dan pembiayaan adalah Return on Invested Capital (ROIC), biaya penggunaan dana (WACC), dan Economic Value Added (EVA). Strategi keuangan matriks adalah pengelompokan perusahaan dalam empat kwadran dan memberikan usulan strategi perusahaan dalam menyelaraskan pertumbuhan perusahaan dengan keputusan investasi dan pembiayaan, sehingga pertumbuhan perusahaan dapat menghasilkan tingkat pengembalian yang mampu menutup biaya penggunaan dana. Dalam upaya mengaplikasikan penggunaan strategi keuangan matrik digunakan contoh 15 perusahaan publik yang beraktiva di atas satu triliun dan 15 perusahaan yang beraktiva di bawah satu triliun berdasar penelitian majalah SWA dan Mark-Plus. Kata kunci: ROIC, WACC, EVA.